797 Obstructive Sleep Apnea is a Risk Factor for Sudden Unexplained Death in Epilepsy (SUDEP). (3rd May 2021) - Soontornpun, Atiwat; Andrews, Noah; Bena, James; Grigg-Damberger, Madeleine; Foldvary-Schaefer, Nancy
Abstract: Introduction: Epilepsy is associated with a substantial risk of morbidity and mortality, including sudden unexplained death in epilepsy (SUDEP). Prior data demonstrated a possible association between obstructive sleep apnea (OSA) based on nocturnal oximetry oxyhemoglobin saturation index (ODI) and risk of SUDEP. We aimed to evaluate the relationship between PSG-defined OSA and SUDEP risk using the revised SUDEP Risk Inventory (rSUDEP-7). Methods: We identified adults with epilepsy who underwent PSG between January 2004 and December 2016 at Cleveland Clinic. OSA was defined as an apnea-hypopnea index (AHI) ≥5 and moderate-to-severe OSA as an AHI ≥ 15. SUDEP risk was determined by the rSUDEP-7. The higher the rSUDEP-7 score, the greater the risk for SUDEP. Associations between rSUDEP-7 score and OSA groups (AHI>15 vs. <15) used Wilcoxon rank sum tests, and multivariable linear models adjusting for age, sex, BMI, and smoking status. Spearman correlations measured relationships between rSUDEP-7 score with AHI and ODI. Results: 214 patients were identified; 134 (62.6%) had OSA, moderate-to-severe in 75 (35%). Those with AHI≥15 were older and more likely to have: pharmacoresistant epilepsy, nocturnal seizures, higher BMI, and longer epilepsy duration (all p<0.05). Median rSUDEP-7 score was 1(0, 3), and > 35% had rSUDEP-7 score of > 3. Patients with moderate-to-severe OSA had higher rSUDEP-7 than those with AHI<15 (p=0.001). Higher AHI and ODI positively correlated with rSUDEP-7 (p=0.002 and p=0.016) while SpO2 nadir negatively correlated with rSUDEP-7 (p=0.007). After adjustment, those with AHI≥15 had mean rSUDEP-7 score 1.14 points (95%CI 0.55–1.72, p<0.001) higher than those with AHI<15. Conclusion: Epilepsy patients with moderate-to-severe OSA, have higher risk of SUDEP based on the rSUDEP-7. Our findings provide further support for routine screening of OSA in epilepsy populations. Support (if any):